Hyper-Securitisation and Belonging: Understanding the Plight of Young Muslims in Melbourne, Australia. Issue 3 (2nd July 2020) - Tittensor, David; Hoffstaedter, Gerhard; Possamai, Adam
Abstract: Following 9/11 the Australian government instituted an unprecedented raft of counter-terrorism measures, which introduced both preventative mass surveillance and pre-crime offences. We suggest that this development represents part of a broader turn in the West towards a "militant democratic" approach to countering violent extremism that, whilst not directly targeting Muslims in name, does so in practice, and has had negative unintended consequences for Muslim diaspora communities. To support our claim we draw on 23 interviews with Muslim youths in Melbourne. In doing so we utilise Ghassan Hage's application of misinterpellation to frame our analysis. We found that Muslim Australians are retreating into their ethno-religious identities as a result of a feeling of misrecognition. We also found that a climate of fear and anxiety is leading to self-censorship and that there was a sense of disconnect between the current leadership and Muslim youth, and that as a result government consultation should extend beyond Muslim peak bodies.